IMPLEMENTASI ZAKAT PADI DI PUTAT GEGER MADIUN PERSPEKTIF FIQH ZAKAT - Kadenun Kadenun Kadenun; Agus Purnomo (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2022)
Zakat is one of the pillars of Islam as a religious obligation imposed on one's wealth according to certain rules. The obligation of zakat is explained in the Law of the Republic of Indonesia Number 23 of 2011 Article 1 paragraph 2, the Qur'an, al-Hadith, and the provisions of zakat are also explained further by the scholars in the books they write. In fact, the implementation of agricultural zakat in Putat Village, Geger District, Madiun Regency, there is a discrepancy in determining the amount of zakat issued by farmers with the provisions explained by zakat fiqh. Therefore, the objectives that want to be known in writing this article are: (1) To find out the awareness of farmers in Putat Village, Geger District, Madiun Regency in issuing agricultural zakat?. (2) To find out the review of zakat fiqh on the implementation of zakat on rice agricultural products in Putat Village, Geger District, Madiun Regency?. This research was conducted qualitatively in Putat Geger Village, Madiun, with data collection procedures through interview, observation, and documentation techniques. The collected data related to the implementation of zakat on rice agricultural products and a review of zakat fiqh on the implementation of zakat on rice agricultural products are analyzed in a correlational manner below. Based on the results of data analysis, it can be said that (1) In the implementation of agricultural zakat in Putat Geger Village, Madiun, namely: Farmers are aware of the obligation of zakat from their agricultural products. However, in spending, they ignore the minimum obligatory zakat (nisab) and mustahiq zakat. Therefore, the implementation of agricultural zakat carried out by the farming community of Putat Geger Madiun Village is very diverse, because they issue and distribute agricultural zakat according to their respective ways and understandings. (2) In terms of zakat fiqh, namely: The zakat issued by the farmers of Putat Geger Madiun Village cannot be said to be completely correct, because in zakat fiqh it has been determined that zakat on agricultural products is 10% in the rainy season, and 5% in the rainy season. dry season, and the zakat must be in the form of rice, it may be in the form of rice if the calculation has been adjusted to the provisions of the fiqh of zakat. Then the distribution must also be given to people who are entitled to receive it in accordance with the provisions described in the Qur'an at-Taubah verse 60.